(untitled) - Lee, Stuart D. (London, 2004)
This practical book addresses the situation by guiding the information professional step-by-step through building and managing an electronic resource collection. It outlines the range of electronic products currently available in abstracting and indexing, bibliographic, and other services and then describes how to effectively select, evaluate and purchase them. Electronic resources are a fast moving area so the new edition of this invaluable guide has been brought completely up to date; emerging new areas such as Virtual Learning Environments and reading/resource list software are considered, and the helpful bibliography of sources is expanded. This invaluable guide identifies best practice and highlights the pitfalls involved in building an electronic resource collection, and the case studies and models used are fully international in their application
Keywords: Collection development ( libraries ),Information resources